Analysis of reflective thinking skills from the perspective of Gregorc’s thinking style - Eko Santoso; Ahmad Yani T; Nurfadilah Siregar; Ade Mirza; Dede Suratman (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2025)
Reflective thinking skills are very important because they are a major part of achieving mathematics learning objectives. However, the reality in the field found problems in students, such as their difficulty in connecting new knowledge with what they already know before. The research conducted aims to describe the ability of reflective thinking in terms of Gregorc thinking style of class XI students at SMA Negeri 8 Pontianak. Descriptive qualitative is the method used in this research with instruments in the form of thinking style tests, reflective thinking ability tests, and interview guidelines. This research involved 4 students of class XI C SMA Negeri 8 Pontianak as subjects. Based on the research results, it was found that subjects with SK thinking style fulfilled all indicators of reflective thinking, subjects with SA thinking style only fulfilled two indicators of reflective thinking, subjects with AK thinking style only fulfilled one indicator of reflective thinking, and subjects with AA thinking style only fulfilled one indicator of reflective thinking. Teachers are advised to consider students thinking styles in learning, while other researchers are advised to examine the comparison of reflective thinking abilities based on differences in thinking styles